Searching for 15-Minute City in Large-Scale Housing Estates: Service Proximity and Diversity in the Context of Population Density - Treija, Sandra; Zaleckis, Kestutis; Bratuškins, Uģis; Bondars, Edgars; Koroļova, Alisa (Landscape Architecture and Art, 2025)
The “15-minute city” concept develops a sustainable mobility paradigm in the context of the city’s central neighbourhoods and outlines clear planning parameters. Since in many cities the majority of the population lives outside the city core, a sustainable city needs the adaptation of the “15-minute city” concept to other contexts. Large-scale housing estates (LHE) are home to a significant proportion of the population in many European cities, especially in Eastern and Northern Europe. LHE were planned with the idea that a neighbourhood is a unit that provides both housing and essential daily needs within walking distance. Although the political, social and economic context has changed significantly since the LHE concept was developed in the mid-20th century, the physical environment of LHE has largely retained the principles of the original urban idea. The aim of the paper is to investigate the multifunctionality of modernist estates and assess the correlation between the centers of gravity associated with four travel destinations - public transport stops, groceries, recreation and education. The study analyzed four LHEs in two cities - Riga and Vilnius, assessing the proximity and diversity of their services in the context of population density. The methodology is based on simulative mathematical modeling. The calculation of the gravitational centrality allowed for a spatially functional analysis, revealing movement patterns and better reflecting the functionality of the city in monofunctionally zoned modernist zones. The main results confirm that in all studied LHEs the average population density within 1 km was higher than the average in both cities. The density of other indicators was different in each case. They even exceeded the average values, showing that modernist-era districts could have the critical mass of objects necessary to implement the 15-minute city concept in the neighborhoods of Riga and Vilnius.